OP03 Reduced need for surgery and medical therapy after early ileocaecal resection for Crohn's disease: Long-term follow-up of the LIR!C trial. (15th January 2020) - Stevens, T; Haasnoot, L; D'Haens, G; Buskens, C; de Groof, E J; Eshuis, E; Gardenbroef, T; Mol, B; Stokkers, P; Bemelman, W; Ponsioen, C
Abstract: Background: The LIR!C trial showed that laparoscopic ileocaecal resection is at least as good as anti-TNF in terms of quality of life and is cost-saving. Current aims were to compare the long-term outcome of both interventions and to identify factors associated with the failure of the initial therapeutic strategy. Methods: Long-term data were retrospectively collected for patients who participated in the LIR!C trial, a multicentre, randomised controlled trial that compared a laparoscopic ileocaecal resection with infliximab for adult patients with non-stricturing and immunomodulator refractory ileocaecal Crohn's disease. Outcomes of interest needed for (re-)surgery or anti-TNF, duration of treatment effect as well as the identification of factors associated with sustained treatment effect. The treatment effect was defined as the time without the need for additional Crohn-related treatment. Potential factors were defined a priori and analysed by multivariable Cox regression analysis. Results: Median follow-up time was 63.5 [IQR 39 – 94.5] months. In the resection group, 18 (26.1%) patients started anti-TNF treatment while none of the patients required a second resection (Figure 1). Twenty-nine (42%) patients did not require additional Crohn-related treatment. In contrast, in the infliximab group, 31 (47.7%) patients underwent a Crohn-related resection. Duration of treatment effect was similar with a median (95% CI) time without additional treatment of 33 (15.1–50.9) and 34 (0–69.3) months in the resection and infliximab group respectively (log-rank p = 0.521). In both groups, prophylactic immunomodulators decreased the risk of additional treatment (HR 0.34 95% CI (0.16–0.69) and HR 0.49 95% CI (0.26–0.93), respectively). Conclusion: This long-term follow-up study of the LIR!C trial showed that after a median follow-up of 5 years the majority of patients who underwent resection were free of anti-TNF treatment, none required a second resection and almost half were free of any additional medical treatment for disease flares. Conversely, almost half of the patients in the infliximab group moved on to a Crohn-related resection. These data support early ileocaecal resection in Crohn's disease patients not responding to conventional treatment.